PENGARUH TERAPI RENDAM KAKI AIR REBUSAN JAHE PUTIH TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA PENDERITA HIPERTENSI - Fiandari, Daffa Shaira; Rohmawati, Zubaida; Salmiyati, Suri (Sekolah Tinggi Ilmu Keperawatan Muhammadiyah Pontianak, 2025)
Objective: To determine the effect of foot soak therapy in boiled white ginger water on blood pressure levels in elderly people with hypertension at BPSTW Budi Luhur. Method: The research design used was Quasy Experimental with a pre-test design and post-test design with control group. The sample taken was 22 people using the total sampling method. The intervention group consisted of 11 respondents who were given foot soak therapy in boiled white ginger water in the morning for 10-15 minutes which was carried out 6 times in 2 weeks and checked pre and post blood pressure. Meanwhile the control group only had pre and post blood pressure checked with a total of 11 respondents. The data analysis technique applied was a paired t-test because the data is normally distributed. Research results: The mean systolic blood pressure in the intervention group was -6.4mmHg with a p-value = 0.008 and the mean diastolic blood pressure was -3mmHg with a p-value = 0.007. The p-value showed <0.05, which means that there is an effect of providing foot soak therapy in boiled white ginger water on blood pressure levels in elderly with hypertension at BPSTW Budi Luhur.